Immunoglobulin G4-Related Disease in The Head and Neck: Two Case Reports and Literature Review - Morteza MAZLOUM FARSI BAF,; Maryam SAHEBARI,; Kamran KHAZAENI,; Zahra REZAIEYAZDI, (Archives of Rheumatology, 2015)
Immunoglobulin G4-related disease (IgG4-related disease) is a fibroinflammatory disorder defined by elevated serum IgG4 level and plasma cells tissue infiltration accompanied by fibrosis or sclerosis. In this article, we report two patients of IgG4 syndrome: a 60-year-old male with complaints of nasal congestion, rhinitis, anosmia and hearing loss, and a 28-year-old female with bilateral orbital and parotid gland swelling. Histopathological findings and high serum IgG4 level confirmed diagnosis of IgG4-related disease. Both patients were treated successfully with glucocorticoids and methotrexate. Herein, we also review clinical presentations of IgG4-related disease in head and neck, and related diagnostic and therapeutic approach.